Analisis Penerapan Artificial Intelligence terhadap Efektivitas Social Media Marketing pada Akun Instagram Cuci Sepatu Kelen dengan Pendekatan Model AIDA - Muhammad Ikhsan Ali; Nur Ahmadi Bi Rahmani; Nurwani Nurwani (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2023)
This research aims to examine the application, obstacles and benefits of Artificial Intelligence ChatGPT on the effectiveness of social media marketing using the Attention, Interest, Desire, Action (AIDA) model approach, especially on the Cuci Shoes Kelen Instagram account. The background to this research is the Industrial Revolution 4.0 which has created an era of digital technology with a high number of internet users in Indonesia, even though digital understanding and literacy is still low. This research uses descriptive qualitative methods by collecting data through virtual ethnography and interviews. The research subjects consisted of two owners of